The Discovery of GIT1/β-Pix Inhibitors: Virtual Screening and Biological Evaluation of New Small-molecule Compounds with Anti-invasion Effect in Gastrointestinal Neoplasms - Wang C; Gu J; Li H; Zhao B; Yu T; Guo CL; Huang M; Jiang W; Ouyang Q (Dove Medical Press, 2024)
Chenkun Wang,1,2,* Jing Gu,2,* Hongwei Li,2,* Bo Zhao,2 Tao Yu,1,2 Chun-Ling Guo,2 Mouxin Huang,2 Weiwei Jiang,1 Qin Ouyang2 1Department of Pharmacy, the Second Affiliated Hospital, Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Medicinal Chemistry, College of Pharmacy, Third Military Medical University, Chongqing, People's Republic of China*These authors contributed equally to this workCorrespondence: Weiwei Jiang, Department of Pharmacy, the Second Affiliated Hospital, Chongqing Medical University, No. 1 Yixueyuan Road, Yuzhong District, Chongqing, 400010, People's Republic of China, Email 304035@cqmu.edu.cn Qin Ouyang, Department of Medicinal Chemistry, College of Pharmacy, Third Military Medical University, No. 30 Gaotanyan St., Shapingba District, Chongqing, 400038, People's Republic of China, Email ouyangq@tmmu.edu.cnBackground and Objective: GIT1 (G-protein-coupled receptor kinase interacting protein-1) has been found to be highly related with cancer cell invasion and metastasis in many cancer types. β-Pix (p21-activated kinase-interacting exchange factor) is one of the proteins that interact with GIT1. Targeting GIT1/β-Pix complex might be a potential therapeutic strategy for interfering cancer metastasis. However, at present, no well-recognized small-molecule inhibitor targeting GIT1/β-Pix is available. Thus, we aim to discover novel GIT1/β-Pix inhibitors with simple scaffold, high activity and low toxicity to develop new therapeutic strategies to restrain cancer metastasis.Methods: GIT1/β-Pix inhibitors were identified from ChemBridge by virtual screening. Briefly, the modeling of GIT1 was performed and the establishment of GIT1/β-Pix binding pocket enabled the virtual screening to identify the inhibitor. In addition, direct binding of the candidate molecules to GIT1 was detected by biolayer interferometry (BLI) to discover the hit compound. Furthermore, the inhibitory effect on invasion of stomach and colon cancer cells in vitro was carried out by the transwell assay and detection of epithelial-mesenchymal transition (EMT)-related proteins. Finally, the binding mode of hit compound to GIT1 was estimated by molecular dynamics simulation to analyze the key amino residues to guide further optimization.Results: We selected the top 50 compounds from the ChemBridge library by virtual screening. Then, by skeleton similarity analysis nine compounds were selected for further study. Furthermore, the direct interaction of nine compounds to GIT1 was detected by BLI to obtain the best affinitive compound. Finally, 17302836 was successfully identified (KD = 84.1± 2.0 μM). In vitro tests on 17302836 showed significant anti-invasion effect on gastric cancer and colorectal cancer.Conclusion: We discovered a new GIT1/β-Pix inhibitor (17302836) against gastrointestinal cancer invasion and metastasis. This study provides a promising candidate for developing new GIT1/β-Pix inhibitors for tumor treatment.Keywords: hit discovery, virtual screening, GIT1, β-Pix, gastrointestinal cancers, invasion